Peripheral leg ischemia detected via intraoperative neurophysiological monitoring during a multilevel complex anterior and posterior operation. Issue 5 (18th May 2020) - Rasouli, Bobak; Pederson, Kristine; Wilkinson, Marshall F; Zarrabian, Mohammad
Abstract: Intraoperative neurophysiologic monitoring is a technique utilized during spinal operations to minimize sensory and motor function morbidity. We herein report a case of a 73-year-old female with renal cell carcinoma and metastatic involvement of the cervical and thoracic spine, who underwent a multilevel complex anterior and posterior operation. Neurophysiological monitoring was able to localize the lower limb ischemia utilizing somatosensory evoked potentials. This prompted intraoperative investigation of the peripheral ischemia, and the patient was found to have an Angio-Seal device embolus in the right popliteal artery that dislodged from the right femoral artery.